UPAYA MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA DENGAN MENGGUNAKAN MODEL PROBLEM BASED INSTRUCTION PADA MATA KULIAH ANALISA VEKTOR UNIVERSITAS GRAHA NUSANTARA PADANGSIDIMPUAN - Lilis Harianti Hasibuan; Susi Sulastri Lubis (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
This research type is Classroom Action Research with student population of sixth semester Graha Nusantara University which amounted to 26 people with object model of learning using problem based instruction as an effort to improve concept understanding student study on vector analysis course. The results showed the results of concept comprehension siclus I test with problem-based instruction obtained percentage of 69.23% sufficient criteria and on the second siclus obtained percentage of 84.62% good criteria. Based on the observation of student activity on the first cycle obtained student activity levels of 70.56% with sufficient category and on the second cycle increased student activity to 86.68% with good category. As for the observation of lecturer ability of cycle I obtained the average value 3,428571 with the category of "Good" and cycle II increased to 4.107143 with the category of "Good". The conclusion of this study is the use of problem based instruction learning models can improve students' understanding of concepts in vektor analysis subjects.